2019
DOI: 10.1038/s41598-018-36999-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in the bone marrow stem cell niche generate specialized microenvironments for the distinct regulation of normal hematopoietic and leukemia stem cells

Abstract: The bone marrow (BM) microenvironment serves as a stem cell niche regulating the in vivo cell fate of normal hematopoietic stem cells (HSC) as well as leukemia stem cells (LSCs). Accumulating studies have indicated that the regeneration of normal HSCs and the process of leukemogenesis change with advancing age. However, the role of microenvironmental factors in these age-related effects are unclear. Here, we compared the stem cell niche in neonatal and adult BM to investigate potential differences in their mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 57 publications
0
24
1
5
Order By: Relevance
“…Besides, the microenvironment of bone marrow could be quite different among different ages which also affect the potential and biodistribution of stem cells. Several researchers investigated that older patients usually have complicated microenvironment changes characterized with dysregulation of metabolism and immune system influenced by various epigenetic factors and signaling networks [45][46][47][48]. In addition, different from our results, a previously [6] published guideline on ONFH suggested that effectiveness of stem cells are limited on preserving joint and the revision was relative high due to young patients.…”
Section: Discussioncontrasting
confidence: 95%
“…Besides, the microenvironment of bone marrow could be quite different among different ages which also affect the potential and biodistribution of stem cells. Several researchers investigated that older patients usually have complicated microenvironment changes characterized with dysregulation of metabolism and immune system influenced by various epigenetic factors and signaling networks [45][46][47][48]. In addition, different from our results, a previously [6] published guideline on ONFH suggested that effectiveness of stem cells are limited on preserving joint and the revision was relative high due to young patients.…”
Section: Discussioncontrasting
confidence: 95%
“…When analyses were limited in patients, age and telomere length were not different according to degree of proliferation nor between disease category. We postulated that age was associated with physiological senescence of BM‐MSCs including telomere shortening, decreased proliferation activity and haematopoiesis support function rather than premature impairment of proliferation which was seen in patients 19‐22 . Interestingly, CXCL12 expression was low in poor proliferating MSCs, which functions HSC maintenance and regulation including quiescence and the ability to induce multilineage reconstitution 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mouse studies have shown that hematopoietic stem cells (HSCs) lose their repopulation capacity while increasing their quiescence and frequency with aging ( de Haan et al., 1997 ; Rossi et al., 2005 ). Aging also favors myeloid, megakaryocytic, and erythroid over lymphoid lineages ( Cho et al., 2008 ; Rundberg Nilsson et al., 2016 ), which has been linked to the influence of intrinsic ( Beerman et al., 2010 ; Chambers et al., 2007 ; Rossi et al., 2005 ) and microenvironmental factors ( Ergen et al., 2012 ; Lee et al., 2019 ; Vas et al., 2012 ). In mouse models, bone marrow (BM) microenvironmental populations that have been reported to be essential for hematopoietic regulation include osteoblasts, endothelial cells, bone marrow stromal cells (BMSCs), and adipocytes ( Acar et al., 2015 ; Ding et al., 2012 ; Ding and Morrison, 2013 ; Zhou et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%